Una investigación sobre habilidades para el aprendizaje científico - Bandiera, J.; Duprè, F.; Ianniello, M. G.; Vicentini Missoni, M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
We report on the natural sciences aspects (physics and biology) of a more complete research on the prerequisites which university teachers expect from freshmen, and the actual capabilities of students at the end of their secondary school. This research has been done on 120 students of 15 classes in Rome (Ltaly). We have tested their ability of transposition among verbal, mathematical and graphical languages, of reading non -elementary graphs, of utilizing empirical data. The conclusion is that at the end of their high school students are largely unprepared to cope with scientific studies, because of their low training to assume analytic attitudes and to operate in formalized manners.